Cooperation Networks and Sustainability: Case Study of a Hotel Network - Silva, Paula Maines; Agostini, Manuela Rösing; Langoski, Leandro Marcio (Revista de Administração da UFSM, 2015)
This study investigates how a hotel cooperation network has fostered sustainable actions with its affiliates. Thus, we sought theoretical references about cooperation networks and sustainability. The research strategy was a single case study, using an interpretive approach with qualitative data. As research results, it is concluded that the associated hotels have developed some sustainable actions, without realizing the impact of these actions on society and the environment. Besides, the network has been more disclosing of sustainable actions realized by its members than an action planner in this area.